DOP90 Physician global assessment of IBD Activity is associated with COVID-19 severity in patients aged less than 50 years. (27th May 2021) - Ricciuto, A; Lamb, C; Benchimol, E I; Walker, G; Kennedy, N; Kuenzig, M E; Kaplan, G; Griffiths, A M; Reinisch, W; Sebastian, S
Abstract: Background: SECURE-IBD is an international database that monitors COVID-19 outcomes in IBD patients. We examined the influence of IBD activity (reflected by Physician Global Assessment (PGA)) on COVID-19 severity, while exploring the modifying effect of age. Methods: We analyzed 3, 028 cases reported to SECURE-IBD from March 13-November 17, 2020. PGA was categorized as remission/mild (reference) vs moderate vs severe. Outcomes used as surrogates of severe SARS-CoV2 infection were hospitalization and a composite of ICU/ventilation/death. Using generalized estimating equations (GEE) to account for clustering by country, we determined the unadjusted association between disease activity and COVID-19 outcomes, overall and by age decade. We included the following covariates in multivariable GEE models a priori : time of COVID-19 diagnosis, age, sex, comorbidities (0, 1, ≥2), IBD type, systemic corticosteroids (CS), anti-TNF monotherapy, anti-TNF plus immune modulator, immune modulator monotherapy, and mesalamine. We included additional covariates (country GDP, race, BMI, anti-integrins and ustekinumab) if they changed the estimate by ≥10%. We also built models stratified by age; the age cut-off for stratification was determined using Joinpoint regression (selecting the age at which outcome rates significantly changed). Results: COVID-19 was more severe in patients with more active IBD: hospitalization rates 19% (remission/mild), 26% (moderate) and 45% (severe); ICU/ventilation/death rates 5% (remission/mild), 6% (moderate) and 12% (severe) (p<0.05, Figure 1). In unadjusted analyses, higher PGA was associated with an increased risk of hospitalization (moderate: OR 1.53, 95% CI 1.24–1.88; severe: OR 3.30, 95% CI 2.44–4.46) and ICU/ventilation/death (moderate: OR 1.44, 95% CI 1.10–1.87; severe: OR 2.58, 95% CI 1.71–3.90). As per Figure 2, the magnitude of association between severe PGA (vs remission/mild) and adverse outcomes was greatest in patients ≤50 years. Joinpoint regression also supported a significant change in the rate of ICU/ventilation/death at 50 years. In multivariable analyses (Figure 3), PGA remained significantly associated with hospitalization, but not ICU/ventilation/death. However, in multivariable analyses stratified by age, PGA was consistently associated with both hospitalization and ICU/ventilation/death in patients ≤50, but not >50 years. Conclusion: Our data suggest an association between IBD activity, as assessed by PGA, and severe COVID-19 outcome with an increased risk in younger patients. Adequate IBD treatment despite the pandemic is needed to avert poor outcome to symptomatic SARS-CoV2 infections.